A Multifunctional AIE Nanoprobe as a Drug Delivery Bioimaging and Cancer Treatment System - Hu, Keqi; Zhou, Daquan; Rao, Linlin; Wang, Peng; Xiang, Chunxiang; Chen, Feng (Frontiers in Bioengineering and Biotechnology, 2021)
Of all malignant brain tumors, glioma is the deadliest and most common, with a poor prognosis. Drug therapy is considered as a promising way to stop the progression of disease and even cure tumors. However, the presence of blood brain barrier (BBB) and blood tumor barrier (BTB) limits the delivery of these therapeutic genes. In this work, an intelligent cell imaging and cancer therapy drug delivery system targeting the blood-brain barrier and the highly expressed transferrin receptors (TfR) in gliomas has been successfully constructed, and an amphiphilic polymer (PLA-PEG-T7/TPE) with aggregation induced emission (AIE) properties has been designed and successfully synthesized. PLA-PEG-T7/TPE self-assembled polymer micelles showed significant AIE effect in aqueous solution with good biocompatibility. Therefore, it can be used for potential biological imaging applications. In addition, drug-carrying micelles showed typical behavior of regulating drug release. Inhibition of cell proliferation in vitro showed that the drug-loaded micelles had dose-dependent cytotoxicity to LN229 cells. In the in vivo anti-tumor experiment, PLA-PEG-T7/TPE/TMZ had the best therapeutic effect. These results indicated that T7 functionalized PLA-PEG was a promising platform for nasopharyngeal cancer drug combination therapy.